2007
DOI: 10.1007/s11101-007-9079-8
|View full text |Cite
|
Sign up to set email alerts
|

Secondary transport as an efficient membrane transport mechanism for plant secondary metabolites

Abstract: Plants produce a large number of secondary metabolites, such as alkaloids, terpenoids, and phenolic compounds. Secondary metabolites have various functions including protection against pathogens and UV light in plants, and have been used as natural medicines for humans utilizing their diverse biological activities. Many of these natural compounds are accumulated in a particular compartment such as vacuoles, and some are even translocated from source cells to sink organs via long distance transport. Both primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 69 publications
2
85
0
2
Order By: Relevance
“…The typical structure of a MATE transporter consists of twelve transmembrane helixes, and it transports several compounds including secondary metabolites utilizing the Na + or H + gradient as a driving force. 7 The mRNA of Nt-JAT1 was expressed in leaves, stems and roots, and the mRNA level increased in response to MeJA treatment in all tissues. To examine whether Nt-JAT1 functioned as a nicotine transporter, the transport activity was measured in a yeast cellular transport system and also in a proteoliposome system.…”
Section: A Novel Mate-type Transporter Nt-jat1 Transports Nicotine mentioning
confidence: 91%
“…The typical structure of a MATE transporter consists of twelve transmembrane helixes, and it transports several compounds including secondary metabolites utilizing the Na + or H + gradient as a driving force. 7 The mRNA of Nt-JAT1 was expressed in leaves, stems and roots, and the mRNA level increased in response to MeJA treatment in all tissues. To examine whether Nt-JAT1 functioned as a nicotine transporter, the transport activity was measured in a yeast cellular transport system and also in a proteoliposome system.…”
Section: A Novel Mate-type Transporter Nt-jat1 Transports Nicotine mentioning
confidence: 91%
“…MATEs involved in xenobiotic detoxification accept a wide range of substrates, but some MATEs have narrower substrate specificities; for example, some MATEs from plants accept citrate, salicylic acid, or flavonoids as substrates (Durrett et al 2007;Serrano et al 2013;Zhao and Dixon 2010). Recent research has revealed the functions of many MATEs in plants (Shoji 2014;Takanashi et al 2014;Yazaki et al 2008).…”
Section: Transporter Familiesmentioning
confidence: 99%
“…The alkaloid transporters also play important roles in plant defense responses against herbivores and microorganisms, reflecting the involvement of alkaloids in plant defenses. ABC and MATE family transporters have been shown to be widely distributed and to be functionally important transporters of secondary metabolites, including not only alkaloids, but also flavonoids and terpenoids (Crouzet et al 2013;Shoji 2014;Yazaki et al 2008Yazaki et al , 2009Zhao and Dixon 2010). The molecular elucidation of alkaloid transporters could contribute to our understanding of a wide range of transport mechanisms.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Medicinal plants usually produce many natural products, such as phenols, flavonoids, quinons, tannins, alkaloids, saponins, sterols, and volatile essential oils. These secondary metabolites have various functions, including antimicrobial, insecticide and appetite suppressant properties (Wilson et al, 1997;Isman, 2000;Liu and Zhang, 2004;Mares et al, 2005;Soylu et al, 2006;Yazaki et al, 2008;Akhtar et al, 2008). Plants in the genus Terminalia, family Combretaceae, comprising of some 250 species, are widely distributed in tropical areas of the world (Fabry et al, 1998).…”
Section: Introductionmentioning
confidence: 99%